2004
DOI: 10.1023/b:mebr.0000027419.79032.bd
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for Zinc Toxicity in Neuroblastoma Cells

Abstract: Zinc is an important component of proteins essential for normal functioning of the brain. However, it has been shown in vitro that this metal, at elevated levels, can be toxic to cells leading to their death. We investigated possible mechanisms of cell death caused by zinc: firstly, generation of reactive oxygen species, and secondly, the activation of the MAP-kinase pathway. Cell viability was assessed by means of the methyl-thiazolyl tetrazolium salt (MTT) assay and confirmed by tetramethylrhodamine methyl e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Since FSH and LH secretion is promoted by FSHRH and LHRH factors which are produced in separated zones in hypothalamus nucleoli [27,29], it is probable that Zn inhibited LHRH production in hypothalamus but did not affect on FSHRH production. Daniels et al reported that zinc is a vital component for normal performance of the brain; however, this ion, at high levels, can be toxic to cells and may induce cell death [18]. Although these findings are similar to those of Dissanayake et al [15], but our findings revealed that serum testosterone value in group T was decreased compared to other groups but statistical analysis did not show any significant changes.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Since FSH and LH secretion is promoted by FSHRH and LHRH factors which are produced in separated zones in hypothalamus nucleoli [27,29], it is probable that Zn inhibited LHRH production in hypothalamus but did not affect on FSHRH production. Daniels et al reported that zinc is a vital component for normal performance of the brain; however, this ion, at high levels, can be toxic to cells and may induce cell death [18]. Although these findings are similar to those of Dissanayake et al [15], but our findings revealed that serum testosterone value in group T was decreased compared to other groups but statistical analysis did not show any significant changes.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, investigation showed that the metal ion such as Zn administered in vivo decrease serum testosterone concentration and change serum concentrations of pituitary hormones in animal models [17]. In addition, it has been shown that in vitro Zn administration, at high dose, can be toxic to cells and can cause their death [18], but other studies showed growth acceleration, testicular development and increase in FSH, LH, and testosterone serum levels after Zn supplementation [19]. Moreover, investigation showed that zinc compounds were more potent for promotion of release of gonadotropins hormone in the ovariectomized animals which pretreated by estradiol and progesterone in a treatment period for 30 days [20].…”
Section: Introductionmentioning
confidence: 99%
“…In toxicological situations, elevated levels can be toxic to cells, a previous study indicating that, in neuroblastoma (N2␣) cell cultures exposed to 100 M of zinc (4 -24 h), loss of viability was attributable to a generation of reactive oxygen species and an activation of the MAP kinase pathway (12). Under conditions of imposed zinc stress (e.g., 300 M Zn 2ϩ ), CHO-K1 cells clearly show the capacity for cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been reported that some harmful effects attributed to zinc deficiency [24][25][26] may also occur with elevated doses of the metal [27]. In healthy humans, given zinc in amounts five times higher than normal for more than 8 days has been shown to produce a decrease in chemotaxis and phagocytosis [13].…”
Section: Discussionmentioning
confidence: 99%